The effectiveness of students redrafting continuous assessment tasks: the pivotal role of tutors and feedback - Dube, Cecilia; Kane, Sandra; Lear, Miriam (Faculty of Education, University of the Free State, 2012)
In order to improve academic language competence, students in two academic literacy modules at the University of Johannesburg were given opportunities to resubmit continuous assessment tasks utilising tutor feedback to improve performance. Despite the potential benefits to the students, not all of them were taking advantage of this opportunity. The main purpose of this study was to establish the reasons for this and to describe a strategy that could be used to enhance learning. Performance records were kept on each student to determine the number of students resubmitting and whether or not marks subsequently improved. Data was also gathered through a questionnaire to establish the reasons for taking advantage or not of the opportunities provided. Small group interviews were conducted to follow up on some questionnaire results. It was found that when students are provided with an opportunity to resubmit assessment tasks, they do benefit, provided that they are sufficiently motivated; clear, specific, constructive feedback is given; and tutoring is of a good quality.
Keywords: Continuous assessment; Tutor development; Feedback; Motivation